تصميم وتطوير منصة رقمية لأدارة الدورات التعليمية بجامعة الوادي - ميلودي, تسنيم; فليون, نور الهدى; هبهوبة, ملاك الرحمان (Université of Eloued جامعة الوادي, 2026)
مشروع EDUC-Gate هو منصة تعليمية إلكترونية تم تطويرها في إطار مذكرة تخرج بجامعة الوادي، تهدف إلى دعم التحول الرقمي في التعليم الجامعي وتسهيل الوصول إلى الدورات التكوينية للأساتذة والطلبة. تناولت المذكرة دراسة واقع الجامعة واحتياجاتها، واستعرضت نماذج ناجحة لمنصات تعليمية مثل "رواق" و"إدراك" للاستفادة من خصائصها. كما ركزت على أهمية التعليم الإلكتروني وأشكاله المختلفة كالتعلم عن بعد والمدمج، ثم تطرقت إلى الوصف التقني للمشروع باستخدام تقنيات مثل HTML، CSS، JavaScript، Laravel، مع اعتماد نماذج UML لتوضيح تصميم المنصة ووظائفها. تهدف المنصة إلى تسهيل تقديم الدورات، إدارة المستخدمين، ومتابعة التقدم التعليمي، وتعتبر خطوة نحو تحسين جودة التعليم العالي بجامعة الوادي.The EDUC-Gate project is an educational platform developed as part of a graduation thesis at the University of El Oued. Its main goal is to support the digital transformation of higher education and facilitate access to training courses for both students and faculty members. The thesis includes a study of the university's current educational context, identifies needs and challenges, and analyzes successful educational platforms such as Rwaq and Edraak for benchmarking. It also highlights the significance of e-learning in modern education, presenting various models like distance learning and blended learning. Technically, the platform was designed and developed using modern web technologies including HTML, CSS, JavaScript, and Laravel, and modeled using UML diagrams to visualize its architecture and features. The platform offers key functionalities such as course management, user account administration, and learning progress tracking—positioning it as a valuable tool for enhancing the quality of education at the University of El Oued.
مذكرة تخرج سنة ثالثة ليسانس إعلام آلي
Keywords: منصة تعليمية - التعليم الإلكتروني - التعلم عن بُعد - التعلم المدمج - التعليم العالي - التحول الرقمي - جامعة الوادي - تطوير البرمجيات - Laravel - نمذجة UML HTML / CSS / JavaScript - إدارة المستخدمين - دورات تكوينية - تجربة المستخدم - برمجة الويب - نظام إدارة التعلم - التعليم المستمر- التكوين الجامعي - الموارد التعليمية المفتوحة - التصميم الموجه للكائنات; Educational Platform – E-Learning – Distance Learning – Blended Learning – Higher Education – Digital Transformation – University of El Oued – Software Development – Laravel – UML Modeling – HTML / CSS / JavaScript – User Management – Training Courses – User Experience – Web Programming – Learning Management System – Continuing Education – University Training – Open Educational Resources – Object-Oriented Design